2013
DOI: 10.4161/cc.23823
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the hierarchy of angiohematopoietic progenitors from human pluripotent stem cells

Abstract: Identification of sequential progenitors leading to blood formation from pluripotent stem cells (PSCs) will be essential for understanding the molecular mechanisms of hematopoietic lineage specification and for development of technologies for in vitro production of hematopoietic stem cells (HSCs). It is well established that during development, blood and endothelial cells in the extraembryonic and embryonic compartments are formed in parallel from precursors with angiogenic and hematopoietic potentials. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 74 publications
1
22
0
2
Order By: Relevance
“…1b). Similar to previous reports 3,4,15 , we found that CD34 + cells from day 10 embryoid bodies expressed the highest levels of key transcription factors for lymphoid differentiation (Supplementary Fig. 4a), specifically showing increased expression of Notch 1 and CD127 (IL7Rα) in the CD34 + CD43 − subset compared to CD34 − CD43 − cells (Supplementary Fig.…”
supporting
confidence: 90%
“…1b). Similar to previous reports 3,4,15 , we found that CD34 + cells from day 10 embryoid bodies expressed the highest levels of key transcription factors for lymphoid differentiation (Supplementary Fig. 4a), specifically showing increased expression of Notch 1 and CD127 (IL7Rα) in the CD34 + CD43 − subset compared to CD34 − CD43 − cells (Supplementary Fig.…”
supporting
confidence: 90%
“…The dermis originates in the mesoderm, where, among other things, the connective tissue, bone, cartilage, blood, and their relevant organs are found 1012. The dermis supports the epidermis and nourishes it 13.…”
Section: Introduction: Definition Of Skin and Fasciamentioning
confidence: 99%
“…77 Because these markers could also be found on differentiated cells at postmesodermal stages, we demarcated mesodermal stage of development as EMH lin 2 , ie, the stage at which cells lack the expression of endothelial (CD31, VE-cadherin), endothelial/mesenchymal (CD73, CD105), and hematopoietic (CD43, CD45) lineage markers. 86,90 On the basis of these analyses, we identified 2 distinct phases of mesodermal development.…”
Section: Mesoderm Induction From Hpscsmentioning
confidence: 99%
“…The developmental progression from HE to hematopoietic progenitors depends on transforming growth factor beta (TGFb) signaling. In an embryoid body differentiation system, treatment of hESCs at the CD31 86,90 Although AHPs expressed the erythroid cell marker CD235a, they had a unique potential to form a broad spectrum of hematopoietic colonies in serum-free medium supplemented with hematopoietic cytokines and FGF2. 86 Gross morphologic examinations of some of these colonies resemble hemangioblast/BL colonies formed by BL-CFCs.…”
Section: Cd45mentioning
confidence: 99%